Influence of Employee Relationship Unit on Team Intention:A Case Study in Implementation of Patient Safety Program - Heru Suswojo; Usman Hadi; Widodo Jatim Pudjirahardjo; Fendy Suhariadi; Agung Dwi Laksono (Institute of Medico-legal Publications Pvt Ltd, 2021)
Incidencesregarding patient safety still occur,and not all are reported to the Hospital Patient SafetyCommittee. The aim studyto analyze the employee relationship influences the work unit staff’s intention inimplementingthe patient safety program—the study was conducted bythe quantitative design of observationalanalytics and through a cross-sectional staff approach. The research sites includedSidoarjo Regional Hospital,Anwar Medika Sidoarjo Hospital, and Ahmad Yani Surabaya Islamic Hospital. The research collects dataduring May–July 2019. The variables consist of employee relationship as the independent variable andintention as the dependent variable. The results show that the development stage’s employee relationshipwas broadly establishing (46.51%), whereas, for the relationship stage, it was a majority of trusts (72.09%).The source intention stage was mostly personal intention(62.79%), and at the intention level, most of thedistal intention was 84.88%. The leadership type affects theworking unit staff’s discretionto implementpatient safety programs in hospitals, with employee relationships as a variable mediator.The study concludedthat the employee relationships had a significant influence on the working unit staff’s intention in hospitalsto carry out patient safety programs. However,employee relationships affect the work unit staff’s intentionto carry out the patient safety program.